Environmental externalities : regional policy and uncertainty - Martins, Manuel Victor (2021)
BAUMOL and OATES [1975] emphasized that negative externalities can induce a breakdown in the conventional convexity assumptions implying that efficiency price loses its normative usefulness as an incentive for the attainment of a social optimum through decentralized market processes.These authors showed that the spatial separation between polluter and pollutee not only contributes to minimize the drawbacks for policy generated by nonconvexities but also induces a superior outcome when compared with the market solution. However, BAUMOL and OATES did not propose any specific policy in order to attain the optimal equilibrium solution implied by their analysis. This paper develops a positive analysis in order to address the main implications and the relative effectiveness of alternative policies inducing spatial separation.